KNOWLEDGE, ATTITUDE & PRACTICE PATTERN OF DIABETIC RETINOPATHY AMONG DIABETOLOGISTS OF VISAKHAPATNAM DISTRICT -A STUDY - P, Viswamithra; Rao N, Bhaskara (International Journal of Clinical and Biomedical Research, 2015)
Background: Diabetic Retinopathy (DR) is the major cause of blindness in working age adults. Because of its asymptomatic nature, most of these patients do not seek ophthalmologists care till the advent of visual loss. Patients who do not receive any form of educational intervention regarding Diabetes and DR, has a fourfold increased risk of developing Diabetic Retinopathy and its delayed recognition. Patients with Diabetes Mellitus (DM) look to their Diabetologists guidance in managing all aspects of their disease including their eye care. According to ICMR guidelines, Diabetologists should discuss visual health with their patients and insist upon annual dilated eye examinations. Present study was undertaken to assess Diabetologists self reported knowledge, awareness and practice patterns of DR relative to the published ICMR guidelines. Methods: A pre tested, semi structured questionnaire was given to 126 Diabetologists practicing in Visakhapatnam district with >5 years of experience in managing DM patients. Results: Study population consisted of 78 General practitioners, 44 General physicians and 4 Endocrinologists. Among 126 Diabetologists, 93.65% (n=118/126) had knowledge about DR. Only 32.53% (n=41/126) had knowledge about recent management modalities of DR. 81.74% (n=103/126) knew about the necessity of annual, fundus examination in DM pts. Only 20.33% (n=26/126) were imparting this knowledge to their patients. Only 6.34% (n=8/126) were advising Ophthalmologist’s evaluation at the time of diagnosis of DM. Conclusion: DR related practice patterns of Diabetologists of Visakhapatnam district significantly differ from recommended strategies for Diabetes eye care . Based upon the results of our study, we suggest the need of certain measures and regulations. KEYWORDS: Diabetes; Diabetic Retinopathy; Diabetes eye care; ICMR guidelines; Physician’s role.